Digital Twin framework for Extended Reality, by integrating Nachi and SCARA Robot in XR-lab - Vilhelmsson, Albin (UiT Norges arktiske universitet, 2022)
Digital Twin is a tool used for monitoring systems and controlling systems at a distance; the twining of systems has been around ever since NASA’s Apollo mission; creating a digital twin lets people monitor the system in real-time. A digital twin also allows for modeling, configuration, testing, optimization, and research under dynamic circumstances; it also provides for hazardous free training on systems that can be hard reach, i.e., offshore. Extended reality is a gathering term for all virtual environments VR, AR, MR, and shared VR, the last one allowing a team to monitor a system together without the need for a headset displaying the information. UiT Narvik has an XR lab based on shared VR; here it is possible to create a collaborative environment around a digital twin. This project is centered around creating a digital twin in the XR lab and making a know-how framework to facilitate a base for more digital twins. The thesis has resulted in two digital twin models that can be used in the XR lab, the robots are located at UiT Narvik, and a proposed method for connecting has been made. The models are created in Unity based on the URDF for each robot; controls have been established for controlling the robots inside the XR environment at the same time as controlling the XR lab. The proposed method for communicating with the robots is to use the Open Sound Control protocol and bridge it with python to the OPC UA server connected to the robots. The know-how framework for integrating a digital twin is presented in the result part of the report.